Implementasi Asuhan Kebidanan Komunitas di Kelurahan Genuk Kecamatan Ungaran Kabupaten Semarang - Suci Rohandayani; Malisa; Oktafiana, Yusfani; Kurnia Dwi Pratiwi; Ratutriya; Putri Cahya; Restika Lelung; Listianingsih, Moneca Diah (Universitas Ngudi Waluyo, 2024)
A community is a collection of people who have at least one of the same characteristics such as geography, occupation, ethnicity, interests and others. Growth is a process of change characterized by an increase in physical size and body shape that can be assessed through measurements of height, weight, and head circumference. Development is a development that occurs in various aspects of a child. The aspects that develop include cognitive, motor, physical, language and speech, psychosexual and independence aspects. One of the contraction and creative ways to train children to regulate breathing patterns and physical activity can provide many benefits for growth and development. Yoga is an activity that does not give wrong or correct judgments but as a fun activity for children. The implementation method used in this community service is health counseling and demonstration about children's yoga to the target of toddlers and mothers of toddlers in Genuk Village RT.01/RW.03 Ungaran District, Semarang Regency. Implementation on May 31, 2024. The participants of this counseling activity were toddlers and mothers of toddlers totaling 15 people. The activity is carried out in stages (1) providing an explanation of the purpose of the activity; (2) distributing pre-tests to target mothers under five years old; (3) providing health counseling on